Injecting bio solids into grass and arable crops. Part II: Development of a shallow application technique - Pullen, D. W. M.; Godwin, R. J.; Grundon, P.; Hann, Michael J. (Elsevier, 2004)
Digested sludge contains valuable crop nutrients but these are largely lost because current application techniques limit where and when it can be applied. Soil injection to depths in excess of 150 mm to reduce odour problems can only be used on fallow land or grass because of the damage it can cause. This leads to applications at high rates being applied with increased environmental risk. The aim of this study was to determine the benefits and limitations of injecting digested sewage sludge into land growing arable crops using shallow, less than 100 mm deep, injection techniques. Agronomic trials conducted over 2 years with winter wheat and rape showed that the crops were surprisingly resistant to mechanical damage during the growing season. Crop yields were not effected by injecting sludge into the crop up to March, equivalent to growth stage 30 in winter wheat, using a conventional tractor-based system working. Injection is possible later in the growing season based on systems with the tractor operating along "tramlines" for field traffic control.